Emigration and the Transnationalization of Sending States’ Welfare Regimes - Jean-Michel Lafleur; Inci Öykü Yener‐Roderburg (Social Inclusion, 2022)
How does emigration affect sending states’ welfare policies? Existing migration literature has identified numerous political, economic, and institutional variables that influence sending states’ approaches towards emigrants’ welfare. However, this literature has neglected broader processes of social transformation in sending states. Using the concept of welfare regime transnationalization, we show more precisely how emigration transforms welfare regimes in their functional, distributive, normative, and politico‐institutional dimensions. This process is nonetheless strongly constrained by domestic politics. To illustrate our analytical framework, we discuss the transnationalization of health policies in Turkey and Mexico.